Mathematical modeling of the sorption isotherms of three varieties of industrial cassava (2013)
A completely randomized design was used to model the sorption isotherms of three types of industrial cassava. The samples consisted of slices (3.6 cm ×0.6 cm ×0.5 cm) of three varieties of cassava: Corpoica Tai, Corpoica Gynes and Corpoica Veronica. Temperature was set at 20 °C, 30 °C and 45 °C. All experiments were performed in triplicate. Data were obtained through an experimental dynamic method to calculate desorption and adsorption isotherms. Results were analyzed for each temperature, and isotherms were calculated for each variety. Isotherms were statistically equal for all temperatures at a 95 % confidence level. The isotherms were adjusted based on mathematical models (GAB, BET, Smith, Oswin, Henderson, and Peleg). The GAB model was considered the most appropriate for data correlation